Tuning the dipolar second-order nonlinear optical properties of 5-π-delocalized-donor-1, 3-di(2-pyridyl)benzenes, related cyclometallated platinum(ii) complexes and methylated salts. Issue 4 (5th January 2017) - Nisic, Filippo; Cariati, Elena; Colombo, Alessia; Dragonetti, Claudia; Fantacci, Simona; Garoni, Eleonora; Lucenti, Elena; Righetto, Stefania; Roberto, Dominique; Williams, J. A. Gareth
Abstract : Increase of the μβ EFISH absolute value by methylation or cyclometallation of novel substituted dipyridylbenzenes. Abstract : The synthesis and characterization of three 5-π-delocalized-donor-1, 3-di(2-pyridyl)benzenes is reported along with that of their related cyclometallated platinum(ii ) complexes and N, N -dimethylated iodide salts. The second-order nonlinear optical (NLO) properties of all the compounds have been determined by the Electric Field Induced Second Harmonic generation technique, showing how the μβ EFISH absolute value of 1, 3-di(2-pyridyl)benzenes can be tuned by the nature of the substituent on position 5 of the central benzene ring, and greatly increased by cyclometallation to Pt or by N -methylation.